Association of Lesion Location and Fatigue Symptoms After Ischemic Stroke: A VLSM Study - Wang, Jinjing; Gu, Mengmeng; Xiao, Lulu; Jiang, Shiyi; Yin, Dawei; He, Ye; Wang, Peng; Sun, Wen; Liu, Xinfeng (Frontiers in Aging Neuroscience, 2022)
Background: Poststroke fatigue (PSF) is a common symptom in stroke survivors, yet its anatomical mechanism is unclear. Our study was aimed to identify which brain lesions are related to the PSF in acute stroke patients. Method: Patients with first-ever acute ischemic stroke consecutively admitted from the first affiliated hospital of University of Science and Technology of China (USTC) between January 2017 to June 2020. Fatigue was scored using the Fatigue Severity Scale. All participants were assessed by 3.0 T brain MRI including diffusion weighted imaging. The infarct lesions were manually delineated and transformed into standard template. Voxel-based lesion-symptom mapping (VLSM) was applied to investigate the association between lesion location and the occurrence and severity of fatigue. The same analyses were carried out by flipping of left-sided lesions. A multivariate logistic regression was applied to verify the associations. Results: Of the 361 patients with acute stroke, 142 (39.3%) patients were diagnosed with fatigue in the acute phase and 116 (35.8%) at 6 months after the index stroke. VLSM analysis indicated clusters in the right thalamus was significantly associated with the occurrence and severity of PSF at 6-month follow-up. In contrast, no significant cluster was found during stroke acute phase. The flipped analysis did not alter the results. Multivariate logistic regression verified that lesion load in the right thalamus (OR 2.67, 95% CI 1.46 - 4.88) was an independent predictor of 6-month PSF. Conclusion: Our findings indicated that lesions in the right thalamus increased the risk of fatigue symptoms 6 months poststroke.